Prognostic Value of Combined HBV pgRNA and MELD Score for Mortality in HBV‐Related Acute‐on‐Chronic Liver Failure: A Single‐Center Retrospective Study - Fenlan Chen; Xiongle Zhang; Chaohui Liu; Wen Lin; Shizhong Lin; Qinqi Wang; Jun Huang; Liping Chen (Health Science Reports, 2025)
ABSTRACT Background and Aims Rapid prognostic assessment of patients with hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) is crucial for optimizing clinical interventions. This study aimed to explore the clinical value of combining Hepatitis B Virus (HBV) pregenomic RNA (pgRNA) with the Model for End‐stage Liver Disease (MELD) score predicting the short‐term outcomes in HBV‐ACLF patients. Methods This retrospective study enrolled 220 HBV‐ACLF patients from Fuqing Hospital in Fujian Province between July 2016 and July 2024. Clinical data collected within 24 h of diagnosis included HBV pgRNA levels, complete blood counts, C‐reactive protein, biochemical profiles, coagulation parameters, and MELD scores. Patients were stratified into survival and non‐survival groups based on 90‐day outcomes. Independent risk factors for mortality were identified through binary logistic regression. Results During the 90‐day follow‐up after hospitalization and discharge, 90 patients died, and 130 survived. Nonsurvivors exhibited significantly higher HBV pgRNA levels (6.07 (5.62–6.71) log10pgRNA [IU/mL] vs. 4.12 [3.81–5.06] log10pgRNA [IU/mL], Z = − 10.14, p < 0.001) and MELD scores (31.88 [27.82–34.66] vs. 21.27 [18.50–23.14], Z = − 12.03, p < 0.001) compared to survivors. Multivariate analysis identified both HBV pgRNA (OR = 12.38, 95% CI = 2.68–57.25) and MELD score (OR = 3.20, 95% CI = 1.33–7.70) as independent predictors of 90‐day mortality (both p < 0.01). The combined model demonstrated superior discriminative ability, with an area under the ROC curve (AUC) of 0.988 (95% CI = 0.978–0.998), significantly outperforming HBV pgRNA alone (AUC = 0.902, Z = 4.487, p < 0.001) and MELD score alone (AUC = 0.977, Z = 2.012, p = 0.044). The optimal cutoff for the pgRNA‐MELD score (−42.253 + 2.516 × log10pgRNA [IU/mL] + 1.165 × MELD) was 0.302 (Youden index = 0.967). Patients with pgRNA‐MELD scores ≥ 0.302 had markedly reduced survival rates (χ² = 253.09, p < 0.01). Conclusion The novel pgRNA‐MELD score effectively predicts short‐term prognosis in HBV‐ACLF patients, offering enhanced clinical utility compared to individual models and guiding timely therapeutic decisions in clinical practice.